LINGUISTIC FEATURES OF PUN, ITS TYPOLOGY AND CLASSIFICATION - Giorgadze, Meri (European Scientific Journal, ESJ, 2014)
This paper focuses on the analysis of pun as one of the categories of wordplay and its manifestation in one-liner jokes in the English languages. The data of this research are all of one-liner jokes containing puns which were collected from different books and online sources. On the basis of various classifications created by different scholars and according to the research material, a new classification of pun as one of the types of wordplay is introduced and defined.